2019
DOI: 10.3389/fneur.2019.00347
|View full text |Cite|
|
Sign up to set email alerts
|

A Chinese Family With Adult-Onset Leigh-Like Syndrome Caused by the Heteroplasmic m.10191T>C Mutation in the Mitochondrial MTND3 Gene

Abstract: Leigh syndrome (LS) is a mitochondrial disease of infancy and early childhood, that is rarely seen in adults. The high degree of genetic and clinical heterogeneity makes LS a very complex syndrome. The clinical manifestations include neurological symptoms and various non-neurological symptoms, with different mutations differing in presentations and therapies. The m.10191T>C mutation in the mitochondrial DNA gene encoding in the respiratory chain complex I (CI) subunit of MTND3 results in the substitution of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…In this study, the six patients with the m.10191T>C mutation were associated with epilepsy, suggesting that this mutation is important in Leigh syndrome with MT-ND3 mutation. Additionally, the results of this study suggested that even the same MT-ND3 mutation may may be strongly associated with epilepsy and these findings are consistent with those of this study (7). The value of this study lies in the fact that its findings are consistent with those of the previous studies and that it undertakes a more focused analysis of the characteristics of epilepsy in Leigh syndrome with the m.10191T>C mutations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, the six patients with the m.10191T>C mutation were associated with epilepsy, suggesting that this mutation is important in Leigh syndrome with MT-ND3 mutation. Additionally, the results of this study suggested that even the same MT-ND3 mutation may may be strongly associated with epilepsy and these findings are consistent with those of this study (7). The value of this study lies in the fact that its findings are consistent with those of the previous studies and that it undertakes a more focused analysis of the characteristics of epilepsy in Leigh syndrome with the m.10191T>C mutations.…”
Section: Discussionsupporting
confidence: 89%
“…Among the various presentations of mtDNAassociated Leigh syndrome, several studies have reported a specific gene related to epilepsy. Some studies have found that m.10191T>C, a major nucleotide change in MT-ND3 gene, is strongly related to epilepsy (7,21). In this study, the six patients with the m.10191T>C mutation were associated with epilepsy, suggesting that this mutation is important in Leigh syndrome with MT-ND3 mutation.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Onset is typically in infancy or early childhood, though adult-onset Leigh syndrome is reported. 2,3 Although it is phenotypically well defined, its vast genetic heterogeneity, with >75 disease-associated genes having been reported to date, makes identification of the genetic defect challenging. 4 Causative pathogenic variants have been identified in both the nuclear genome and the mitochondrial genome (mtDNA), and these variants affect various aspects of mitochondrial function including structural subunits and assembly factors of respiratory chain complexes (e.g., NDUFS2 [MIM: 602985] 5 and SURF1 [MIM: 185620] 6 ), Krebs cycle components (e.g., PDHA1 [MIM: 300502] 7 ), mitochondrial protein translation (e.g., MTFMT [MIM 611766] 8 ), and valine metabolism (e.g., ECHS1 [MIM 602292] 9 ).…”
mentioning
confidence: 99%